Coeliac disease, gluten‐free diet and the development and progression of albuminuria in children with type 1 diabetes. Issue 6 (14th June 2013) - Gopee, Esha; van den Oever, Eva LM; Cameron, Fergus; Thomas, Merlin C
<x xml:space="preserve">Abstract</x> Objectives Although a diagnosis of coeliac disease (CD) may be confronting to children with type 1 diabetes and their families, we hypothesize that children with CD have lower urinary albumin excretion, a marker of renal dysfunction. Research design Twenty‐four children with type 1 diabetes and biopsy‐proven CD, on a gluten‐free diet for at least 1 yr, were recruited from a single paediatric diabetes clinic alongside 55 children with type 1 diabetes but without CD matched for age, gender, duration of diabetes, and glycaemic control. Results Despite comparable diabetes exposure, glycaemic control and nutritional status, children with type 1 diabetes and CD had a lower urinary albumin creatinine ratio than in diabetic subjects without CD (0.9 ± 0.3 mg/mmol vs. 1.6 ± 0.3 mg/mmol; p = 0.01). Participants with CD also showed slower progression in albuminuria over 5‐yr of follow‐up while a small but significant increase was observed in the children with diabetes alone (1.6 ± 0.3 mg/mmol; follow‐up 2.4 ± 0.5 mg/mmol; p = 0.02). Conclusions As urinary albumin excretion is continuously associated with the risk of kidney disease, it is possible to speculate that CD or its management confers a degree of renoprotection. Larger studies are required to test this hypothesis.